From Contemplative Penitent to Annihilated Soul: The Recasting of Mary Magdalene in Marguerite Porete’s Mirror of Simple Souls - Dubois, Danielle C. (Journal of medieval religious cultures, 2013)
In her late thirteenth-century dialogue, the Mirror of Simple Souls, Marguerite Porete reframes the origin and the function of penitential practice by drawing on conceptions that associate Mary Magdalene with original sin and personal salvation. With the cult of the Magdalen flourishing in the Low Countries and across Europe, Porete adopted the saint to concretize her doctrine of the annihilated soul. This article argues that the saintly sinner’s conversion is no longer defined through chastity, contrition, and the performance of works of goodness in the Mirror but, rather, through detachment, pure intention, and divine love. Furthermore, an analysis of “the consideration of the Magdalen” reveals that Porete’s interpretation of the metaphor of tilling the earth presents a riposte to the exegetical tradition that considered Mary Magdalene a symbol of sin. As such, Porete recasts the contemplative and penitent Magdalen of popular culture into a model of the annihilated soul.